Actualization of the Use of Artificial Intelligence (AI) in Developing Islamic Education in the Era of Society 5.0 - Moh. Zarkani; Burhanudin Burhanudin; Lalu Pradipta Jaya Bahari; Samsul Bahri; Syafnan Syafnan; Doli Witro (Khazanah Pendidikan Islam, 2024)
The rapid development of artificial intelligence technology has opened up new opportunities in the transformation of education, including Islamic education. This research aims to analyze the use of AI in personalizing Islamic learning in the era of Society 5.0, with a constructivism-based theoretical approach. The method used is a qualitative-descriptive analysis of the literature and phenomena related to the application of AI in Islamic education. The results show that AI has great potential in creating learning that is more adaptive and meets individual needs, especially through the use of personalization algorithms and in-depth data analysis. This article makes a novel contribution by offering a new perspective on the application of AI technology based on constructivism theory, which highlights the importance of the interaction between technology, learners and the social environment. The implication is that the application of AI can encourage innovation in curriculum design and teaching strategies, while ensuring alignment with Islamic values in the digital age.